Boron Nitride Nanotube Coatings for Thermal Management of Printed Silver Inks on Temperature Sensitive Substrates. (7th May 2021) - Wagner, Kaitlin; Paquet, Chantal; Martinez‐Rubi, Yadienka; Genest, Marc; Guan, Jingwen; Sampson, Kathleen L.; Kim, Keun Su; Kell, Arnold J.; Malenfant, Patrick R. L.; Lessard, Benoît H.
Abstract: Printed electronics provide inexpensive and light weight electrical components to fuel emerging applications. One major challenge is the high temperature required to sinter conductive metal inks, which leads to thermal degradation of the substrate and subsequently poor performance. A boron nitride nanotube (BNNT) interfacial film is reported for thermal management in rapid processing of a printable silver molecular ink platform using intense pulsed light (IPL) sintering techniques. The inclusion of BNNT thin films of varying surface concentrations deposited between the substrate and the printed features reduces thermal damage to the substrate during sintering while simultaneously improving electrical performance, achieving a sheet resistance value as low as 140 mΩ sq −1 . A wide range of sintering energies ranging from 2.0 and 3.2 J cm −2 are investigated along with printed trace widths ranging from 5 mil (0.127 mm) to 20 mil (0.508 mm). Increases in the rate of cooling and in the current carrying capacity are confirmed with the inclusion of the BNNTs. Overall the thin coating of BNNTs presents no drawbacks while significantly improving the electrical properties of IPL sintered conductive traces and thus represents a simple approach that will advance the adoption of IPL for fabricating printed electronic components. Abstract : A thermally conductive boron nitride nanotube (BNNT) thin film is interposed between printed silver features and a temperature‐sensitive substrate to minimize heat accumulated during intense pulsed light sintering. The BNNT films improve the silver trace morphology, mitigate substrate warping, and are shown to be actively dissipating heat through the BNNT network without sacrificing electrical performance of the silver.